Efeitos da termotolerância celular nas lesões por radiofrequência no miocárdio de ratos - Santos, Luis Felipe Neves dos [UNIFESP] (2012)
The delayed effects of radiofrequency (RF) seem to be related to the extent of the lesion. We evaluated the effects of thermotolerance on the dimensions and remodeling of RF lesions in the rat myocardium and whether RF promotes apoptosis in the region surrounding acute ablation lesions in a rat model. Methods: Two groups were evaluated: treated (TG, n=22), subjected to thermal shock (a bath at 42oC for 10 min.), and control (CG, n=22, bath at a 37ºC for 10 min.). After 48 hours, an RF lesion (customized catheter, tip 4.5 mm in diameter; 12 Watts; 10 seconds) was performed on the free wall of the left ventricle (LV). The rats were sacrificed 2 hours (n=10 per group) and 4 weeks (n=12 per group) after RF for macroscopic and histological analysis of the lesions and echocardiogram was obtained at 4 weeks to assess ventricular remodeling. Additional animals (n=30) were killed after 2 hours for apoptosis evaluation using histological (H.E. - hematoxylin and eosin, TdT-mediated dUTP Nick End-Labeling [TUNEL] assay), immunohistochemical (anti-BAD and anticaspase 3 antibodies) analysis (n = 18) and anti-BAD Western Blotting analysis. Results: There was no difference between groups regarding the size of acute (CG 27± 2 mm2 vs. TG 27±3 mm2) and chronic lesions (CG 17 ± 1 mm2 vs. TG 19 ± 1 mm2). Histology revealed coagulative necrosis in the acute lesions and welldemarcated fibrosis, with no difference between groups. The echocardiogram revealed dilation of the cavities and moderate systolic dysfunction. The diameters of the left atrium and of the left ventricle (LV) (diastolic, TG 9.8±0.9 mm vs. CG 9.6±1.1 mm, p=NS), the ejection fraction and the fractional shortening of the transverse area of the LV (TG 45±3% vs. CG 39±3%. p=NS) did not differ between groups. TUNEL assay revealed positive luminescent reaction cells suggesting apoptosis, however IHQ, Western Blotting and histology were negative. Conclusion: Thermotolerance does not reduce the size and remodeling of RF lesion in the rat myocardium and RF ablation does not promote apoptosis in the periphery of the myocardial lesion.